Biology and Management of Exploited Crab Populations Under Climate Change 2011
DOI: 10.4027/bmecpcc.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Stock-Recruitment-Environment Relationship in a Portunus pelagicus Fishery in Western Australia

Abstract: Blue swimmer crab (Portunus pelagicus) fisheries in Western Australia have generally been considered robust to recruitment overfishing, as the minimum legal size for retention of these crabs in both the commercial and recreational crab fisheries are set well above the size at sexual maturity allowing crabs to spawn at least once before entering the fishery. However, the Cockburn Sound crab stock suffered a recruitment collapse, with three key factors: (a) the fishery is near the edge of this species distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
(22 reference statements)
0
9
0
2
Order By: Relevance
“…The development of ovaries and eggs in the blue swimming crab is strongly controlled by temperature. Even water temperature was being the only factor that can influence the life cycle and the change of population structure for a long period (De Lestang et al, 2003;De Lestang et al, 2010). Also, the temperature of the blue swimming crab can growth is 25-32 ºC (Romano & Zeng, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The development of ovaries and eggs in the blue swimming crab is strongly controlled by temperature. Even water temperature was being the only factor that can influence the life cycle and the change of population structure for a long period (De Lestang et al, 2003;De Lestang et al, 2010). Also, the temperature of the blue swimming crab can growth is 25-32 ºC (Romano & Zeng, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Los datos y los análisis indicaron que los humedales son importantes para los stocks de jaiba porque H/M y SH se relacionan directamente con r. El stock de la zona 3 tiene la mayor r, la mayor H/M y la mayor SH. Esto puede indicar que la producción de huevos aumenta con la abundancia de hembras (Lasker, 1985) y la abundancia de humedales favorece el reclutamiento (Carmona, 2009;De Lestang et al, 2010;Fischer & Wolff, 2006). Dada la importancia de este posible hallazgo, en el futuro se deben incorporar mayor cantidad de datos para mejorar el análisis de sensibilidad.…”
Section: Discussionunclassified
“…For P. pelagicus, BT explained considerable variance and had negative correlations with BTs >25 • C in the TS. Studies have revealed that the water temperature is a factor that controls the ovarian development and spawning of P. pelagicus [10,24,58]. Moreover, Qari and Aljarari [58] mentioned that temperature is a critical environmental parameter that plays a role in limiting the distribution and activity of P. pelagicus in the Red Sea.…”
Section: Effects Of Ocean Environmental Variables On the Swimming Crabsmentioning
confidence: 99%
“…This information can be used to implement sustainable fisheries through methods, such as harvest strategy planning [1], ecosystem management [2,3], spatial management [4][5][6], and bycatch reduction [7]. Environmental variables, such as water temperature, salinity, water depth, and increased productivity, may be significant factors driving changes in population patterns [8,9], catch rates [10][11][12], reproductive and recruitment strategies [13][14][15], and spatiotemporal distribution [16,17].…”
Section: Introductionmentioning
confidence: 99%